Comparison between Spectral-domain and Swept-source OCT Angiography Scans for the Measurement of Hyperreflective Foci in Age-related Macular Degeneration - Gissel Herrera, MD; Yuxuan Cheng, PhD; Yamini Attiku, MD; Farhan E. Hiya, MD; Mengxi Shen, MD, PhD; Jeremy Liu, MD; Jie Lu, PhD; Alessandro Berni, MD; Omer Trivizki, MD; Jianqing Li, MD; Robert C. O’Brien, PhD; Giovanni Gregori, PhD; et al. (Ophthalmology Science)
Purpose: Spectral-domain OCT angiography (SD-OCTA) scans were used in an algorithm developed for swept-source OCT angiography (SS-OCTA) scans to determine if SD-OCTA scans yielded similar results for the measurement of hyperreflective foci (HRF) in intermediate age-related macular degeneration (iAMD). Design: Retrospective study. Participants: Forty eyes from 35 patients with iAMD. Methods: Patients underwent SD-OCTA and SS-OCTA imaging at the same visit using a 6 × 6 mm OCTA scan pattern. Hyperreflective foci were detected as hypotransmission defects on en face structural images generated from a custom slab positioned 64 to 400 μm beneath Bruch’s membrane and confirmed on corresponding B-scans by the presence of well circumscribed lesions within the neurosensory retina or along the retinal pigment epithelium (RPE) that are of equal or greater reflectivity than that of the RPE. Two independent graders evaluated the en face images and B-scans for the presence of these lesions. Outlines of HRF on en face images were generated using a published semiautomated algorithm developed for SS-OCTA scans and manually corrected by the graders when necessary. The total area measurements of the HRF within the 5-mm circle centered on the fovea were obtained from the algorithm using each imaging method. Main Outcome Measures: Agreement of the square root (sqrt) of the HRF total areas obtained from SS-OCTA and SD-OCTA. Results: The sqrt total areas of the HRF from both imaging modalities were highly concordant, with Lin’s concordance correlation coefficient (rc) of 0.94 (95% confidence interval: 0.86–0.97; P < 0.001). The mean sqrt of the total HRF area measurements identified using SS-OCTA and SD-OCTA imaging were 0.390 mm (standard deviation [SD]: 0.170) and 0.393 mm (SD: 0.187), respectively with mean difference of −0.003 (95% confidence interval: −0.021 to 0.015; P=0.76). Conclusions: Spectral-domain OCT angiography scans yielded results similar to SS-OCTA scans when the same semiautomated algorithm was used to measure HRF in the central 5 mm of the macula, suggesting that either a single 6 × 6 mm SD-OCTA or a SS-OCTA scan pattern can be used to determine the total macular HRF burden in eyes with age-related macular degeneration. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.